2015
DOI: 10.1111/ibi.12272
|View full text |Cite
|
Sign up to set email alerts
|

The winter diet of theAtlanticPuffinFratercula arcticaaround theFaroeIslands

Abstract: Wanless, Sarah. 2015. The winter diet of the Atlantic puffin Fratercula arctica around the Faroe Islands. Ibis, 157 (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Frederiksen et al 2012, Fayet et al 2017) and the climate factors driving synchrony in seabird population dynamics in such a threatened and declining species as the Atlantic puffin (BirdLife International 2018). We have illustrated the value of tracking data to produce co variates describing climate conditions specific to seabird's non-breeding distributions, rather than relying on large-scale climate indices, which cover a multitude of factors but do not bring us much closer to understanding the mechanisms behind climate-driven mortality (Harris et al 2015). Although we found little evidence of ETCs in wintering areas as a common driver of adult survival, populations most ex posed to extreme storms may experience negative effects.…”
Section: Discussionmentioning
confidence: 84%
“…Frederiksen et al 2012, Fayet et al 2017) and the climate factors driving synchrony in seabird population dynamics in such a threatened and declining species as the Atlantic puffin (BirdLife International 2018). We have illustrated the value of tracking data to produce co variates describing climate conditions specific to seabird's non-breeding distributions, rather than relying on large-scale climate indices, which cover a multitude of factors but do not bring us much closer to understanding the mechanisms behind climate-driven mortality (Harris et al 2015). Although we found little evidence of ETCs in wintering areas as a common driver of adult survival, populations most ex posed to extreme storms may experience negative effects.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have reported shifting summer foraging areas in response to changing prey availability in razorbills [15, 61], whilst puffins have been recorded as maintaining overwintering locations despite changed environmental conditions [25]. Puffins are also known to lower their trophic position and adopt more opportunistic foraging strategies during the harsher winter months [26, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Our aims were to 1) test whether differences in overwinter survival were associated with changes in locations within the North Sea and/or trophic position, 2) assess whether such responses were similar in the two species and 3) investigate whether any observed changes in locations and diet could be related to the abundance and distribution of potential prey species. For this final test we collated data on the distribution and abundance of lesser sandeel ( Ammodytes marinus ), sprat ( Sprattus sprattus ) and herring ( Clupea harengus ), lipid-rich high quality prey that are known to be common in the diet of puffins and razorbills during the breeding and winter seasons across the North Sea [26, 27, 37]. We also extracted distribution and abundance data, as well as isotope measurements for snake pipefish ( Entelurus aequoreus ), as this normally rare and nutritionally poor species showed a short-lived population explosion in 2007 and 2008, and was found in the diets of a wide range of marine predators [24, 64].…”
Section: Introductionmentioning
confidence: 99%
“…Since we detected various differences in adult and chick diets, this method is likely imperfect and even our dual-methodology here may be inadequate to fully assess adult puffin invertebrate consumption. Although our decisions regarding which taxa represent intentional consumption were largely substantiated by the available literature (Piatt, 1987; Falk et al, 1992; Bowser et al, 2013; Harris et al, 2015), it’s possible that adult puffins exploit invertebrate prey resources more broadly than currently thought.…”
Section: Discussionmentioning
confidence: 99%